#EvenMore than just a brand of soap: a case study analysing LUX soap's use of Instagram - Venter, L'André (Centre for Film and Media Studies, 2021)
This research investigates the ways in which Unilever's LUX soap has repositioned their brand away from their historical association with beauty pageants. This research aims to unpack the ways in which Instagram is utilised by LUX soap to effectively communicate a distinct brand personality. This research identifies that the repositioning of the brand on Instagram was achieved through a strategy that integrated social media influencers and brand events, whilst incorporating social marketing. Not only does this research focus on LUX's branding on Instagram, it critically engages with the content from a postfeminist perspective. This is the secondary theoretical engagement of this work. The paper highlights the ways in which the content is postfeminist in nature and how this was incorporated into the branding messages. The main focus of this dissertation is the #MoreThanYouCanSee and #EvenMore LUX soap campaigns. Through a mixed methodology of interviews, content analysis, and survey the paper focuses on the ways in which LUX created a relationship with their customers on Instagram and effectively repositioned the brand. The research suggests that three key techniques were repeated on Instagram to effectively create new associations with the LUX brand during the #MoreThanYouCanSee and #EvenMore extension campaign. The paper, furthermore, suggests that the LUX soap campaign employs postfeminist rhetoric in their Instagram strategy. This dissertation argues that the development of a strategy consisting of branded events, social media influencers, and social marketing content allowed LUX soap to reposition their brand.